Comparative Perspectives on Work-Life Balance and Gender Equality: Fathers on Leave Alone - O'Brien, Margaret; Wall, Karin (Life Course Research and Social Policies, 2017)
Sociology of Family, Youth and Aging; Family; Gender Studies